THE INFLUENCE OF THE USE OF CONCEPT MAP IN THE CONCEPTUAL UNDERSTANDING PROCEDURES (CUPs) LEARNING MODEL ON PHYSICS LEARNING OUTCOMES FOR CLASS XI SMAN 1 2x11 ENAM LINGKUNG - Mutya, Dian (PILLAR OF PHYSICS EDUCATION, 2024)
Learning that takes place in educational units requires strategies to achieve learning objectives. Learning outcomes indicate the attainment of learning goals. The learning outcomes of students in physics subjects at SMAN 1 2x11 Enam Lingkung class XI Science still have not reached the minimum learning completeness set by the school. This fact is related to students’ low motivation and interest in learning and the learning model that has been determined has not been implemented optimally and is not in accordance with the students’ character. One of the ways to overcome this problem is to apply the Conceptual Understanding Procedures (CUPs) learning model accompanied by making concept maps. This study aims to determine whether there is a significant influence from the use of concept maps in the Conceptual Understanding Procedures (CUPs) learning model on physics learning outcomes for class XI SMAN 1 2x11 Enam Lingkung. The sort of inquire about carried out was Quasy Experimental Design with a Posttest Only Control Design.. The research results are based on an analysis of the similarity test of two means using the t test. At a significance level of 0.05, tcount = 2,14 greater than ttable = 1,67, leading to the acceptance of the  Hi accepted. Thus, it is determined that there is a significant influence from the use of concept maps in the Conceptual Understanding Procedures (CUPs) learning model on physics learning outcomes for class XI SMAN 1 2x11 Enam Lingkung.